New Technology: Electric Vehicles That Continue to Develop in the Fuel Era, Which is Experiencing Many Changes in Quality and Quantity: Electric vehicles are starting to exist and also preparation of energy supporting infrastructure - Rahmadina, Fadila; syarifudin, ichwan; rahmadhina Putri, Nabila (SAINFIS: Jurnal Sains Fisika, 2024)
Abstract There are many enthusiasts and the release of new innovations among foreign countries regarding electric vehicles which continue to develop in the new era of human resource development. Apart from this, there is also an impact on other fuels such as BBM which continues to experience changes in quality, coupled with the more economical power costs needed to refuel electric vehicles. Basically, people like things that are profitable and economical for their daily needs and are balanced with other needs, so that there is also environmental health by using without fuel which makes pollution thicker, let’s call it Pollution. This research method uses mixed methods, with a Concurrent Mixed Method research design. Where this quantitative data was obtained using a questionnaire via Google Form media. So that the results of the research method carried out obtained quite satisfactory results from 93 respondents. The Ministry of Energy and Mineral Resources, in carrying out the energy transition that previously came from fossil energy to renewable energy, targets that the use of EBT has reached 23% by 2025. In this way, it can help the economic growth cycle and also fulfill the national energy supply. There are also long-term public facilities such as environmentally friendly and more affordable as well as requests such as holding battery charging depots for electric motorbikes to make it easier for users to use electric motorbikes without feeling afraid of running out of energy. The implementation of electric vehicles in Indonesia is a major challenge in the limited electricity supply. Keywords: Operational Costs, Energy, and Electric Vehicles